Orthorexia nervosa – a new health problem - characteristics - Olejniczak, Dominik; Skonieczna, Joanna (Journal of Education, Health and Sport, 2018)
Orthorexia nervosa is a relatively new health problem. In the world scientific literature there are only a few publications in this subject. This can be the reason why uniform diagnostic criteria for orthorexia have not been developed yet. Therefore, further research into the cause, course and treatment of orthorexia is needed. Regarding the characteristics of the phenomenon, it is necessary to consider orthorexia as a public health problem.